Pony [compact disc] - Peck, Orville (Sub Pop, 2019)
Combining the lulling ambience of shoegaze with the iconic melodies and vocal prowess of classic American country music, enigmatic outlaw cowboy. Orville Peck, croons love and loss from the badlands of North America. His upcoming debut album, delivers a diverse collection of stories that sing of heartbreak, revenge and the unrelenting tug of the cowboy ethos.